2017
DOI: 10.12783/dteees/icesee2017/7862
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydraulic Retention Time on MFC-A2/O Process for Domestic Wastewater Treatment

Abstract: Abstract. A 10L scale MFC coupled A2/O system was built, with the anaerobic tank as anode chamber to remove carbon and the anoxic tank as cathode chamber to denitrify. This coupled system could achieve max output current after 30 days. During the study phase, the hydraulic retention time (HRT) was optimized to improve wastewater treatment efficiency and power generation. The results showed that the coupled system could obtain best pollutants removal effect when HRT=16h. Compared with control reactor, concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Apart from this, some researchers thought high HRT may reduce the concentrations of substrate and the cell metabolism at the anode chamber (Liu et al, 2008), which inhibited the MFC reactor's production of energy. A reduced HRT results in more degradation of the substrate used for generating electricity at a unit time in the MFC system, thereby enabling biomass to convert energy (Luo et al, 2017). However, this scenario may require a higher concentration of EBA or stronger biofilm, which could oxidize more organics in a shorter time.…”
Section: Santos Et Al (2017)mentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from this, some researchers thought high HRT may reduce the concentrations of substrate and the cell metabolism at the anode chamber (Liu et al, 2008), which inhibited the MFC reactor's production of energy. A reduced HRT results in more degradation of the substrate used for generating electricity at a unit time in the MFC system, thereby enabling biomass to convert energy (Luo et al, 2017). However, this scenario may require a higher concentration of EBA or stronger biofilm, which could oxidize more organics in a shorter time.…”
Section: Santos Et Al (2017)mentioning
confidence: 99%
“…Luo et al (2017) found that longer HRT could even cause full oxidization of organics in domestic wastewater.In the study byGe et al (2013), they found that the removal efficiencies of COD were approximately 40-60% and 70-80% at the HRT of 10 h and 24 h, respectively, whilst continuously operating an osmotic MFC for domestic wastewater treatment. Similarly, Haavisto et al (2017) employed a two-chamber up-flow MFC to produce electricity from xylose, in which decreasing the HRT from 3.5 d to 0.17 d resulted in reduced removal of COD from 95% to 78%.…”
mentioning
confidence: 99%